Answer:
00,000
Step-by-step explanation:
bc you times it all toghther
Answer:
6 x 4 = 24, 24 divided by 2 = 12(area of 1 triangle)
12 x 2(two triangles) = 24
5 x 6 = 30(area of 1 slanted rectangle)
30 x 2(two rectangles) = 60
6 x 6 = 36(area of bottom square)
Add all given AREAS:
24 + 60 + 60 = 144 mm2 is your answer.
By some properties of logarithms, rewrite the equation as
![2\log(a-2b) = \log(a) + \log(b) \\\\ \log(a-2b)^2 = \log(ab)](https://tex.z-dn.net/?f=2%5Clog%28a-2b%29%20%3D%20%5Clog%28a%29%20%2B%20%5Clog%28b%29%20%5C%5C%5C%5C%20%5Clog%28a-2b%29%5E2%20%3D%20%5Clog%28ab%29)
so that
(<em>a</em> - 2<em>b</em>)² = <em>ab</em>
Expand the left side:
<em>a</em> ² - 4<em>ab</em> + 4<em>b</em> ² = <em>ab</em>
Rearrange terms to get a quadratic equation in <em>a</em>/<em>b</em> :
<em>a</em> ² - 5<em>ab</em> + 4<em>b</em> ² = 0
<em>b</em> must be greater than 0, otherwise log(<em>b</em>) doesn't exist, and the same goes for <em>a</em>. So we can divide by <em>b</em> ² to get
<em>a</em> ²/<em>b</em> ² - 5<em>a</em>/<em>b</em> + 4 = 0
Factorize and solve for <em>a</em>/<em>b</em> :
(<em>a</em>/<em>b</em> - 4) (<em>a</em>/<em>b</em> - 1) = 0
==> <em>a</em>/<em>b</em> = 4 or <em>a</em>/<em>b</em> = 1
However, if <em>a</em>/<em>b</em> = 1, then <em>a</em> = <em>b</em> makes <em>a</em> - 2<em>b</em> = -<em>b</em>. But we must have <em>b</em> > 0, so we omit the second solution and end up with
<em>a</em>/<em>b</em> = 4
Answer:
222
Step-by-step explanation: